Knowledge, Attitude, And Practices of The Educated Women of North India Toward Cervical Cancer - Ishita Miglani; Urvashi Gandhi; Poonam Laul (Indian Journal of Community Medicine)
Cervical cancer is a largely preventable disease that claimed the lives of more than 300 000 women in 2018. Hesitation to adopt cervical cancer screening strategies motivated us to find out the knowledge gaps and attitudes of the educated section toward these practices. An in-depth knowledge of this aspect will help us comprehend the barriers that are deterring women from accepting these practices. A cross-sectional survey was conducted from November 1, 2021, to November 30, 2021, to assess the public knowledge, attitudes, and practices regarding cervical cancer. The self-designed online questionnaire was shared on social media such as Telegram, WhatsApp, LinkedIn, and Facebook. Girls and women aged 15 years and more studying in educational institutions or those who have completed their graduation were asked to fill out the questionnaire if willing to do so anonymously. 824 respondents filled out the online survey. 75% of the respondents had good knowledge about pap smear and HPV vaccination. Only 80 respondents (9.7%) were vaccinated against HPV. 255 (30.9%) had been screened with a pap smear at least once in their lifetime. Screening with pap smear was never performed in 412 subjects, which constituted 50% of the respondents. A poor knowledge about the eligibility of pap smear and the availability of HPV as a screening modality may have contributed to a poor conversion to the regular practice of screening modalities. Awareness drives need to focus on these issues.